Anxiety in youth with and without specific learning disorders: exploring the relationships with inhibitory control, perfectionism, and self-conscious emotions - Lievore, Rachele; Cardillo, Ramona; Mammarella, Irene Cristina (Frontiers in Behavioral Neuroscience, 2025)
IntroductionSince early research on Specific Learning Disorders (SLD), their relationship with emotional issues have been recognized, although emotional factors have received less attention compared to the cognitive processes related with academic achievement.MethodsThis study aimed to investigate mechanisms that may increase vulnerability to generalized and social anxiety in youth with SLD, compared to their non-diagnosed peers. We examined cognitive factors (inhibitory control), personality traits (self-oriented, socially prescribed perfectionism), and self-conscious emotions (shame, guilt). The sample included 134 individuals aged 10 to 16, divided into two groups: 67 with SLD and 67 without diagnoses, matched by age, sex, and IQ. Participants completed questionnaires on anxiety, perfectionism, and selfconscious emotions, alongside an inhibitory control task.ResultsFindings revealed that those with SLD reported higher generalized and social anxiety, poorer inhibitory control, greater socially prescribed perfectionism, and more shame than nondiagnosed peers. Socially prescribed perfectionism was found to increase the risk of generalized anxiety in participants with SLD, while both socially prescribed perfectionism and shame were predictors of social anxiety across both groups. Finally, self-oriented perfectionism seemed to be associated with lower social anxiety in the SLD group.DiscussionThese findings suggest that interventions should address risk and protective factors, focusing on reducing anxiety and fostering adaptive self-regulation strategies.